The effect of a magnetic field on the motion of electrons for the field emission process description - Lebedynskyi, S.O.; Miroshnichenko, V.I.; Kholodov, R.I.; Baturin, V.A. (Вопросы атомной науки и техники, 2015)
The Schrödinger equation is solved for the wave function of an electron moving in a superposition of external constant and uniform electric and magnetic fields at an arbitrary angle between the field directions. The changing of the potential barrier under influence of the magnetic field parallel to the metal surface is shown. Розв’язується рівняння Шрьодінгера для хвильової функції електрона, що рухається в суперпозиції зовнішніх постійних і однорідних електричному і магнітному полях під довільним кутом між їх напрямками. Показано зміну потенційного бар'єру під впливом магнітного поля, що паралельне поверхні. Решается уравнение Шредингера для волновой функции электрона, движущегося в суперпозиции внешних постоянных и однородных электрическом и магнитном полях под произвольным углом между их направлениями. Показано изменение потенциального барьера под влиянием магнитного поля, параллельного поверхности